2013
DOI: 10.1542/peds.2013-0878
|View full text |Cite
|
Sign up to set email alerts
|

Nonmedical Vaccine Exemptions and Pertussis in California, 2010

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Previous studies have shown that nonmedical exemptions (NMEs) to immunization cluster geographically and contribute to outbreaks of vaccinepreventable diseases such as pertussis. The 2010 pertussis resurgence in California has been widely attributed to waning immunity from acellular pertussis vaccines. WHAT THIS STUDY ADDS:This study provides evidence of spatial and temporal clustering of NMEs and clustering of pertussis cases and suggests that geographic areas with high NME rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
135
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 187 publications
(149 citation statements)
references
References 26 publications
7
135
0
5
Order By: Relevance
“…This method identifies localized, statistically significant (P < 0.05) geographic clusters of events adjusting for multiple testing (27,28,(36)(37)(38). We evaluated potential clusters between a 0-and 200-km radius by using the free software program SaTScan, version 9.4 (38).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This method identifies localized, statistically significant (P < 0.05) geographic clusters of events adjusting for multiple testing (27,28,(36)(37)(38). We evaluated potential clusters between a 0-and 200-km radius by using the free software program SaTScan, version 9.4 (38).…”
Section: Resultsmentioning
confidence: 99%
“…However, if one takes a closer look at the community level, there is substantial local variation in vaccination rates throughout the United States (27)(28)(29)36). It is the local variation in vaccination rates that is of concern because more than 90% of the community needs to be vaccinated against pertussis for herd/community immunity to be effective (39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But herd immunity breaks down when coverage drops even in small pockets of otherwise well-vaccinated regions. Omer and colleagues found that this effect may have contributed to a 2010 pertussis outbreak in California that infected more than 9,000 individuals 6 . "The clustering of refusals was associated with the clustering of pertussis, " says Omer.…”
Section: Forgotten Foesmentioning
confidence: 99%